Palavra, vozes e memória discursiva: concepções sobre ética do tradutor e intérprete de língua de sinais - Santiago, Vânia de Aquino Albres (2021)
The performance of Sign Language Translators and Interpreters (TILS) covers language, culture, and otherness in an intense process of interaction. The Interpretation/Translation involves the meeting of different individuals who, given their linguistic/cultural/historical differences, carry a singular character in their words concurrent to how they display their social voices. Which discourses contribute to the comprehension of ethical conceptions concerning otherness and responsibility towards the Brazilian deaf community? Based on this fundamental inquiry, the research questions are: a) considering the relation of otherness between deaf individuals and listeners, what characteristics contribute to the recognition of TILS as an ethical profession in the face of the Brazilian deaf community?; b) what ethical situations and dilemmas drive the production of discourses about the performance of TILS professionals in Brazil? In addition to formal training, to proficiency in sign language, to technical knowledge about translation and interpretation, and to cultural immersion as a member of the Brazilian deaf community, we present the hypothesis that, to work as a TILS professional with this community, it is needed to engender a notion of ethics to defend sign language and the linguistic right of deaf people. As a theoretical-methodological framework, we have adopted Bakhtin's Circle theory on the dialogic nature of language, which reflects and refracts the social values of those who have put it into work. Therefore, the general objective of this research is to analyze how the conception of ethics in the work of TILS is presented in the discourses of the Brazilian deaf community and how these conceptions influence the construction of the training of this professional. The specific objectives are: a) to analyze how different discursive subjects emerge in statements about the performance of TILS in Brazil; b) to promote the debate on otherness and belonging to the deaf community with regard to TILS and GI listening participants as mediators in different contexts; c) reflect on the ethical foundations of the activity of TILS and GI and on their formation. The corpus of this research is composed of three groups of discourse: 1) texts of TILS graduation speeches at a higher level written and spoken by listeners; 2) text of official speeches from a deaf person known to be representative of the Brazilian deaf community; and 3) the texts of the two main codes of ethics of TILS profession which were made collectively. The analysis is organized from the description and understanding of the context of production, circulation and reception of these discourses and the collation of words or terms to trace the path of analysis and interpretation of the text itself, based on the linguistic-enunciative-discursive perspective, identifying statements that relate to the movement of discourses on the work of TILS and GI. We also present, as one of the axes of analysis, the creation of a discursive network in the constitution of the corpus and, from it, we seek to understand the concepts of ethics, and propose ways for the formation and reflection of moral norms from the concept of otherness, responsibility, and representativeness, in the perspective of discursive ethics, based on Bakhtin's philosophical formulations